Examinations of Bilateral Epileptiform Activities in Hippocampal Slices Obtained From Young Mice - Liu, Haiyu; Carlen, Peter L.; Zhang, Liang (Frontiers in Cellular Neuroscience, 2021)
Bilateral interconnections through the hippocampal commissure play important roles in synchronizing or spreading hippocampal seizure activities. Intact hippocampi or bilateral hippocampal slices have been isolated from neonatal or immature rats (6–7 or 12–21 days old, respectively) and the mechanisms underlying the bilateral synchrony of hippocampal epileptiform activities have been investigated. However, the feasibility of examining bilateral epileptiform activities of more developed hippocampal circuitry in vitro remains to be explored. For this, we prepared bilateral hippocampal slices from C57 black mice, a strain commonly used in neuroscience and for genetic/molecular modifications. Young mice (21–24-day-old) were used in most experiments. A 600-µm-thick slice was obtained from each mouse by horizontal vibratome sectioning. Bilateral dorsal hippocampal and connecting dorsal hippocampal commissure (DHC) tissues were preserved in the slice and extrahippocampal tissues were removed. Slices were recorded in a submerged chamber mainly at a room temperature (21-22ºC). Bilateral CA3 areas were monitored by extracellular recordings, and unilateral electrical stimulation was used to elicit CA3 synaptic field potentials. The unilateral stimulation could elicit population spikes in the contralateral CA3 area. These contralateral spikes were attenuated by inhibiting synaptic transmission with cobalt-containing medium and were abolished when a cut was made at the DHC. Self-sustained and bilaterally correlated epileptiform potentials were observed following application of 4-aminopyradine and became independent after the DHC cut. Bilateral hippocampal activities were detectable in some slices of adult mice and/or at 35-36ºC, but with smaller amplitudes and variable waveforms compared to those observed from slices of young mice and at the room temperature. Together, these observations suggested that examining bilateral epileptiform activities in hippocampal slices of young mice is feasible. The weaknesses and limitations of this preparation and our experimentation are discussed.